The effect of built environments on the walking and shopping behaviors of pedestrians; A study with GPS experiment in Sinchon retail district in Seoul, South Korea. (June 2019) - Hahm, Yeankyoung; Yoon, Heeyeun; Choi, Yunwon
Abstract: With this research, we aim to identify built environmental components of retail districts that affect pedestrian behaviors and influence their shopping behavior. We conducted GPS experiments to observe visitors' choice of walking route—pedestrian volume and visit duration—and the questionnaire survey to obtain their records of shopping on where and how much they spent in the Sinchon retail district of Seoul, South Korea. We then employed a path analysis to assess the causal relationship between the built environment, walking behavior, and shopping behavior. We found that pedestrians prefer streets with safety from vehicles, high design quality; higher hierarchy, centrality, and provision of resting places or other street amenities; and that all of these variables also increase pedestrian's visit duration and induce spending at stores on the street. This study would provide design guidelines to municipalities or private retailers looking to revitalize retail districts through environmental improvements. Highlights: Pedestrians are willing to visit the streets of higher hierarchy and centrality. High-quality street conditions positively affect walking and shopping activities. Streets with various options for shopping retain pedestrians for long time. The distance from transportation facilities does not guarantee retails' revenue. Customers prefer the variability of the store-mix.